2022
DOI: 10.1108/jhti-01-2022-0033
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life and the quest for authenticity in touristic experiences among Turkish tourists

Abstract: PurposeDiscussions of authenticity in touristic experiences indicate that it is a significant area in the search for meaning. This study aims to demonstrate that the quest for authenticity in a tourist experience begins in the pre-travel period by associating it with meaning in life.Design/methodology/approachData were collected via survey from 356 people planning to participate in tourism activities. The survey included demographic questions, the meaning in life scale and the quest for authenticity (QfA) scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 110 publications
(228 reference statements)
0
1
0
Order By: Relevance
“…Perceived authenticity: Authenticity is an attribute, a reflection of characteristics, or a current state of existence (Park et al , 2019). It aims to portray tradition by establishing a probable link to the past (Seyitoglu, 2021; Zhang and Yin, 2020) and it is crucial for tourism products and services (Cinar et al , 2022; Genc and Genc, 2022). Previous studies showed that perceived authenticity is a significant part of the tourists' food experiences (Atsiz et al , 2022b).…”
Section: Resultsmentioning
confidence: 99%
“…Perceived authenticity: Authenticity is an attribute, a reflection of characteristics, or a current state of existence (Park et al , 2019). It aims to portray tradition by establishing a probable link to the past (Seyitoglu, 2021; Zhang and Yin, 2020) and it is crucial for tourism products and services (Cinar et al , 2022; Genc and Genc, 2022). Previous studies showed that perceived authenticity is a significant part of the tourists' food experiences (Atsiz et al , 2022b).…”
Section: Resultsmentioning
confidence: 99%